Pengembangan Katalog Digital untuk UMKM Berbasis Bambu untuk Meningkatkan Pemberdayaan Ekonomi Lokal: Studi Kasus di Desa Sugihwaras, Indonesia - Mohammad Anshori; Eko Arief Cahyono; Muhammad Arifin; Umma Shofiatuz Zuhroh; Eva Pitri Dispayanti (Program Studi Teknik Mesin, Fakultas Teknik Universitas Bengkulu, 2026)
This study aims to enhance the competitiveness of bamboo-based micro, small, and medium enterprises (MSMEs) through the development of a digital product catalog in Sugihwaras Village, Indonesia. The program was conducted using the Asset-Based Community Development (ABCD) approach, which emphasizes local potential and community participation. The intervention included product documentation, digital catalog creation, and training in digital marketing and product photography. A total of 15 MSME actors participated in the program. Quantitative findings indicate a 70% increase in participants’ understanding of digital marketing concepts and a 60% expansion in product promotion reach through online platforms. In addition, the number of product inquiries increased by approximately 45% within one month after catalog dissemination. The results demonstrate that digital catalog implementation significantly improves marketing effectiveness and strengthens business networking among MSMEs. Furthermore, this initiative contributes to sustainable local economic development by integrating community assets with digital technology. This study highlights the importance of digital transformation in empowering rural MSMEs and can serve as a replicable model for similar communities.